Why are women entrepreneurs missing out on funding? Reflections and considerations - Executive summary - Fackelmann, Surya (European Investment Bank, 2020)
The study assesses the access-to-risk-capital conditions for women-driven companies in Europe in comparison to the US and Israel to contextualise emergent cross-country and regional barriers and gaps. The study finds that while women-led companies still account for a small portion of deal flow and overall volume invested the rate of growth has increased across all the examined regions. Nevertheless, structural inequalities and persistent biases both on the supply of and demand for finance for women-driven companies still hinder the transition to a more balanced, more accessible and ultimately better functioning funding environment. For this reason the study puts forth and analyses a number of options and considerations - both financial and policy related - that could help accelerate this transition. As multiple evidence-based studies and data points show, women's economic empowerment makes not only ethical but also economic and business sense. InnovFin Advisory carried out the study with support of PitchBook, complementing market data with interviews of market practitioners of the European Venture community and other stakeholders.